2010
DOI: 10.2106/jbjs.h.01831
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of the Fulcrum Bending Radiograph in Scoliosis Correction with Alternate-Level Pedicle Screw Fixation

Abstract: To our knowledge, this is the first study to demonstrate the predictive value of the fulcrum bending radiograph in the context of alternate-level pedicle screw fixation in patients with adolescent idiopathic scoliosis. Curve flexibility may dictate the degree of the fulcrum bending correction index, whereby a curve that is less flexible may achieve a greater fulcrum bending correction index. The fulcrum bending radiograph has potential predictive utility. In addition, pedicle screw constructs appear to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…It is well known that to achieve a certain degree of correction, the more rigid the curve, the more correction ability is required [2,10]. In our study, a similar significant high correlation was noted between Angle XF to that of FBCI and XFI.…”
Section: Discussionsupporting
confidence: 83%
“…It is well known that to achieve a certain degree of correction, the more rigid the curve, the more correction ability is required [2,10]. In our study, a similar significant high correlation was noted between Angle XF to that of FBCI and XFI.…”
Section: Discussionsupporting
confidence: 83%
“…However, a significant correlation has been found between the number of implants and the curve correction using a multi-center database of AIS patients [11]. It has also been reported that increasing the number of implants can improve the correction of curves with higher stiffness, as determined by the fulcrum bending radiograph [10]. The discrepancies between the results of this work and the clinical studies may be explained by the fact that there exist considerable differences on how the increased control provided by adding additional implants have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Basic deformity reduction techniques associated with the modern segmental spinal instrumentation systems for posterior spinal fusion involve vertebral translation, rod derotation, apical vertebral derotation, bilateral apical vertebral derotation, direct vertebra derotation, compression and distraction, and in situ rod contouring [7,8]. In order to apply certain correction techniques and to have a better control on the deformed spine, there has been a noticeable trend among spine surgeons to use more and more pedicle screws [9][10][11]. Nowadays, pedicle screws are frequently placed bilaterally at each vertebra included in the fusion, but some surgeons recommend fewer screws [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the FBCI took curve flexibility into account, it was considered a better method than the correction rate for comparing curve corrections with different instrumentation system. Cheung et al [19] prospectively assessed the predictive value of the FBR in AIS curve correction in the context of alternate level pedicle screw fixation of the MT curve. A mean FBCI of 122% was obtained, and they draw the conclusion that pedicle screw constructs have a better ability to correct scoliosis compared to hooks and hybrid constructs.…”
Section: Discussionmentioning
confidence: 99%